ROLE OF PANGLIMA LAOT INSTITUTION ON ACHIEVING SUSTAINABLE CAPTURE FISHERIES IN SABANG - Baskoro Pakusadewo; Akhmad Solihin; Ernani Lubis (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
Abstract The objectives of this study was to analyze the regulation system and to recommend the management of empowerment strategy for Panglima Laot Lhok Iboih, Sabang. This study used qualitative approach with a triangulation method. Data were collected by means of purposive and snowball sampling. Analysis used in this study were normative juridical, describtive, and SWOT analysis. The results obtained from this study were Panglima Laot Lhok Iboih has implemented several roles: (1) Closed area system in the waters area of Lhok Iboih as conservation and marine tourism area, then the prohibitation of the use of destructive tools and methods of fishing, prohibition day for fishing, prohibition to harvest ornamental fish, and prohibition all activities that damage the environment in the Lhok Iboih. (2) Implement sanction for anyone who break the rules, that is: consisting of payment penalty in the form of money, livestock, fishing gears seizure, reconducted the Khanduri Laot; Enpowerment strategies of Panglima Laot were conducted by benefiting the strengths and opportunities (SO), which were: the increase of communities role on socializing sea customary law to tourists, collaborative cooperation between Panglima Laot and tourism operators on operational monitoring of SATGAS, the increase of institutional capacity building of Panglima Laot for monitoring and managing fisheries through coaching and training in collaboration with government and NGOs, the providing of infrastructure and facilities coordinated with goverment. Keywords panglima laot, fisheries management, reinforcement of institution institution system